The relationship between expression level and gene polymorphism of inflammatory factors and sepsis risk - Shubao Wang; Tianyu Liang; Chulei Zhang (Scientific Reports)
Abstract The biomarkers associated with sepsis have not yet been completely elucidated. The objective of the current article is to investigate whether inflammatory factors act as risk factors for sepsis. The study included 320 adult patients with sepsis, which were enrolled as experimental group. In addition, 560 healthy individuals from the same period were selected as the control group. Cytokine expressions were measured using flow cytometry with fluorescence, and gene polymorphisms were analyzed through the PCR-RFLP technique. Significantly higher expression levels of IL-1, IL-6, IL-10, and TNF-α, were detected (p < 0.05). This study also identified specific polymorphisms IL-1B -511 C/T, IL-10 -1082 G/A, IL-6 -174 G/C, and TNF-α -308 G/A, that were significantly associated with an increased risk of sepsis (p < 0.05). The expression levels of IL-1, IL-6, IL-10, and TNF-α are associated with an increased risk of sepsis. Additionally, the polymorphisms IL-1B -511 C/T, IL-6 -174 G/C, IL-10 -1082 G/A, IFN-γ + 874 A/T, and TNF-α -308 G/A are also linked to sepsis risk in the Chinese population.